Subwavelength-Structured High-Efficiency Nanophotonic Coupler for Air Top-Cladded Silicon Waveguide - Yuhan Sun; Ting Li; Peiji Zhou; Yi Zou (IEEE Photonics Journal, 2021)
Efficient coupling between an optical fiber and silicon waveguide has been a major practical challenge for silicon photonics since the first day due to the huge mode size mismatch between them. In this paper, we propose a subwavelength structured edge coupler for efficient coupling light into/out from air top-cladded silicon waveguides. Through refractive index engineering, we demonstrate a single-step patterned coupler with a coupling loss of ∼2.5 dB for the wavelength range from 1.5 μm to 1.65 μm.